Global Monetary Conditions versus Country-Specific Factors in the Determination of Emerging Market Debt Spreads - Dailami, Mansoor; Masson, Paul R.; Padou, Jean Jose (2012)
US interest rate policy is shown to have a significant influence on emerging market bond spreads, but it is important to allow for non-linearities: US interest rates affect secondary market spreads differently, depending on countries' debt levels. Moderate debtors suffer little impact from an increase in US interest rates, while a country close to the borderline of solvency would face a much steeper increase in its spread. A 200 basis points increase in US short-term interest rates would increase emerging market spreads by 6-65 bps, depending on debt/GNI ratios.